Analisis Kompaaratif Stabilitas Kimia dan Fisika Paracetamol pada Sediaan Padat dan Cair - Anisa Anisa; Annisa Normiani Putri; Nor Latifah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Paracetamol is one of the most widely used analgesic-antipyretic drugs and is available in various formulations, including solid tablets and liquid syrups, which differ significantly in long-term stability. This review analyzes data from ten journal studies (2013–2024) comparing the stability of paracetamol in different dosage forms. A literature review method was employed to assess physical and chemical stability under various storage conditions. Solid dosage forms, such as tablets, generally exhibit excellent long-term stability. When stored in sealed packaging at 30 °C/75% RH, tablets maintained potency and low impurity levels for up to five years. In contrast, liquid formulations, especially oral suspensions, degrade more rapidly once opened. For example, an opened Panadol® suspension retained acceptable quality for about five months under optimal conditions (refrigerated, protected from light) and degraded faster (around 3.5 months) under high temperatures. The main degradation product, p-aminophenol (PAP), remained below 0.005% in tablets but exceeded the 0.1% limit in most opened suspensions.Formulation factors, including pH and cosolvent use (e.g., glycerin, PEG 400), significantly affected liquid stability. Syrups with PEG 400 + glycerin maintained stable pH levels (5.6–6.8). In conclusion, solid forms are more stable than liquids, and careful formulation and adherence to storage guidelines are essential to ensure product quality.